Neurodevelopmental Outcomes of Premature Infants Born at ≤32 Week Gestation Age with Post-Hemorrhagic Hydrocephalus Treated with Ventriculo-Peritoneal Shunt - Ana Rita de Miranda Neves (2021)
Introduction: In preterm newborns, Post-hemorrhagic Hydrocephalus (PHH) can lead to changes in development. There is no consensus on its treatment yet. The aim of this study is to evaluate the neurodevelopmental outcomes in preterm newborns with PHH treated with ventricular-peritoneal shunt (VPS). Materials and Methods: We evaluated all cases with ≤32 weeks gestational age who developed PHH and were treated with VPS between January 2007 and December 2017. An assessment of neurodevelopmental outcomes was made through their medical records at 3 years of age. Results: Cerebral Palsy (CP) was the most registered pathology (68.8%), followed by epilepsy (43.8%). No cases of bilateral deafness, use of hearing aids or total blindness were documented. Six (37.5%) of the children wore glasses. Regarding the Griffiths Mental Development Scales, 4 (50%) had General Quotient score corresponding to developmental delay. Delay was mostly observed in the locomotor subscale (75%), followed by Eye and Hand Coordination (62.5%) and Hearing and Speech (50%). Realization (37.5%) and Personal Social (12.5%), had the lowest number of cases with delay. Discussion: The results obtained were consistent with previous studies. The pathophysiology of brain injury in these children is multifactorial and the findings might be related to pressure effects of hydrocephalus and parenchymal injury. Conclusion: CP, epilepsy and developmental delay may have a higher risk of developing in infants where VPS was used. No cases of hearing impairment were found, which may indicate that this pathology is not related to the use of VPS. Infants treated with VPS for PHH represent a high-risk group for the development of adverse neurodevelopment outcomes.